Analisis Pengaruh Campuran Biodiesel terhadap Performa dan Emisi Gas Buang Mesin Diesel Common-Rail - Pratiwi, Ilham Ayu Putri; Krisnaputra, Radhian; Bahiuddin, Irfan; Djati, Isworo; Nugraha, Sindhu Arya (Jurnal Mekanik Terapan, 2025)
This study aims to analyze the effect of biodiesel blend variations on the performance and exhaust emission characteristics of a diesel engine equipped with a Common-Rail Direct Injection (CRDI) system. The experimental tests were conducted using two types of fuel, namely B50 (50% biodiesel and 50% diesel) and B100 (pure biodiesel). The evaluated parameters included fuel consumption (FC), specific fuel consumption (SFC), and exhaust emissions consisting of CO, CO₂, NO, NOₓ, O₂, and SO₂. Tests were performed at three engine speeds (800, 1000, and 1500 rpm) and three electrical load levels (600 W, 1000 W, and 2000 W). The results showed that both FC and SFC increased with higher engine speed and load, where the average SFC of B100 was 5–15% higher than that of B50 due to the lower calorific value of biodiesel. In terms of emissions, the use of B100 reduced CO concentration by up to 10% compared to B50, while NOₓ emissions increased by approximately 15–25% at higher speeds. SO₂ emissions were recorded at 0 ppm under all test conditions, indicating that biodiesel is sulfur-free. These findings confirm that pure biodiesel can be effectively utilized in modern diesel engines with common-rail injection systems, providing good combustion efficiency and contributing to the reduction of exhaust gas emissions.